The Urgency of Islamic Boarding Schools in the Contemporary Era - Muhdi, Ali; Sudadi, Sudadi; Antoni, Antoni; Daelami, Muhammad Syadid; Judijanto, Loso (Al-Hijr: Journal of Adulearn World, 2023)
Basically, the era of globalization has both good and bad impacts on children. One of the most important factors in development and education is morals, because currently morals are increasingly deteriorating. Therefore, the role of parents is very important in determining the right education so that children have good growth and character development. This research aims to determine the urgency of Islamic boarding schools in the contemporary era. This research uses quantitative methods using survey models and in-depth interviews. The survey tool used by researchers is Google From. Then the researchers also conducted in-depth interviews with parents and boarding school administrators. The results of this research show that Islamic boarding schools can be a means of helping a child's moral development in the contemporary era. The conclusion of this study explains that the role of parents is very important in choosing education for children. Therefore, the limitation of this research is that the researcher did not conduct a survey of children's development outside the Islamic boarding school so they cannot compare how a child's morals are, therefore the researcher hopes that future researchers can conduct research on how a child's morals are outside the Islamic boarding school.